Restoring colorado river ecosystems : - Adler, Robert W. (Island Press, 2007)
Restoring Colorado River Ecosystems explores the many questions and challenges surrounding the issue of large-scale restoration of the Colorado River basin, and of large-scale restoration in general. Robert W. Adler evaluates the relationships among the laws, policies, and institutions governing use and management of the Colorado River for human benefit and those designed to protect and restore the river and its environment. He examines and critiques the often challenging interactions among law, science, economics, and politics within which restoration efforts must operate. Ultimately, he suggests that a broad concept of “restoration” is needed to navigate those uncertain waters, and to strike an appropriate balance between human and environmental needs.